Symptomatological significance and characterization of susceptibility / resistance group among low land rice cultivars towards stem rot of rice in Manipur valley - and RANJIT SHARMA, JITEN KONTHOUJAM*, G.K.N. CHHETRY (Indian Phytopathology, 2007)
Stem rot of rice caused by Sclerotium oryzae. Catt., has rapidly spread throughout the Manipur valley during the past 9 years ( 1997-2005). It has infected all cultivated low land rice cultivars either of local or exotic origin to Manipur. None of the 33 cultivars studied in current roving and fixed location surveys during 2004-2005 Kharif, were resistant or highly resistant against the disease. The degree of susceptibility among cultivars differed with marked symptomatological difference in size, number and position of lesions on the infected stems above the field water level. Highly susceptible cultivars exhibited more number of lesions (3.0-8.5), larger coalesced lesion size (72.6 sq.mm - 406.2 sq.mm) at crop maturity and extended to higher positions on the stems up to 6.6 inches above the soil, in fields with 2" water level during cropping period. The size, number and positions of the lesions decreased with increasing resistance of the individual cultivars.